State of research on the genus Disticholiparis Marg. & Szlach. (Orchidales, Malaxidinae) - Margońska, Hanna B. (Biodiversity: Research and Conservation, 2006)
The article is an introduction to taxonomic problems within the recently described genus Disticholiparis Marg. & Szlach. Genetic variation in the ITS region was analysed, which proved the distinct character of the genus Disticholiparis, as compared with other taxa of the former genus Liparis. A determination key to Disticholiparis and closely related Asiatic genera of the Malaxidinae, as well as a description of the genus are presented. Goals and methods of further research are listed and briefly characterized.